Subsurface Stress Measurement in GIS Epoxy Composite by Using LCR Waves - Zhouyiao Zou; Yanpeng Hao; Yao Zheng; Weiming He; Fangyuan Tian; Lin Yang; Licheng Li (Energies, 2020)
Internal stress in basin insulators of gas-insulated metal-enclosed switchgear (GIS) can lead to cracks, which affects the safe operation of these apparatuses. In this research, we proposed a subsurface internal stress measurement method for GIS epoxy composites. This method is based on an ultrasonic longitudinal critically refracted (LCR) wave technique. In this study, some epoxy composite specimens were synthesized with similar materials and manufacturing processes to those of 252 kV GIS basin insulators. An ultrasonic stress measurement system that utilized the LCR wave technique was set-up to investigate the relationship between stress and LCR wave propagation time, as well as to measure the compressive stress of the epoxy specimen within 0–50 MPa. The results show that LCR wave propagation time linearly decreased when stress increased in the subsurface zone and the acoustoelastic coefficient was −4.95. We found the relative errors of stress measurements to be less than 13%.